Psoas muscle mass index and peak expiratory flow as measures of sarcopenia: relation to outcomes of elderly patients with resectable esophageal cancer - Zhang, Mingzhi; Xiong, Yaqiong; Chen, Mengzhou; Xu, Dafu; Xu, Keping; Tian, Wenze (Frontiers in Oncology, 2023)
The objective of this study is to investigate whether the evaluation of postoperative outcomes or overall survival in patients who undergo surgery for esophageal cancer can be achieved by assessing sarcopenia using psoas muscle mass index and peak expiratory flow.Methods: This retrospective study analyzed the clinical data of 356 elderly patients ( ≥ 65 years) who had undergone radical surgery for esophageal cancer. Muscle mass and muscle strength were assessed by psoas muscle mass index (bilateral psoas area/height 2 ) and peak expiratory flow, using preoperative computed tomography and spirometry, respectively. Sarcopenia is defined as a condition where both the psoas muscle mass index and peak expiratory flow fall below their genderspecific cutoff values. Survival and postoperative complications were compared between patients with and without sarcopenia.Results: Out of the 356 elderly individuals diagnosed with esophageal cancer, 84 patients (23.6%) were found to have sarcopenia. The group with sarcopenia showed a notably higher occurrence of postoperative pneumonia (29.8% vs 16.9%, P < 0.001) and anastomotic leak (9.5% vs 3.7%, P < 0.05) compared to those without sarcopenia. Additionally, a multivariate analysis concluded that sarcopenia independently acted as a risk factor for postoperative pneumonia, possessing an odds ratio of 1.90 (P < 0.05). The survival rate after 3 years for individuals with sarcopenia was considerably lower than those without sarcopenia (57.8% vs 70.2%, P < 0.05). Sarcopenia was identified as an unfavorable prognostic factor for overall survival, with a hazard ratio of 1.51 (P < 0.05).Conclusions: Preoperative sarcopenia diagnosed by psoas muscle mass index and peak expiratory flow is associated with reduced overall survival and adverse postoperative outcomes among elderly individuals suffering from esophageal cancer.